The banquet in Palmyrene funerary contexts - Audley-Miller, L (Peeters Publishers, 2018)
The aim of this study is to examine the range of sociocultural significances that banqueting reliefs had for the people of Palmyra, who commissioned and saw these images, in the first three centuries AD. The paper commences by exploring the various interpretations of what the iconography of reclining to dine meant at Palmyra. It then examines how and why the social level of patrons represented in these reliefs changed over time. These alterations in use are outlined here, because who was represented in the banquet, as well as what was represented, reinforced and informed the social resonance of the image. The Palmyrene banqueting motif was used as a prestigious expression of ancestry with each client adjusting and personalising this established iconographic template to present a selective view of their own family history. In order to examine these personal receptions and reinterpretations in action, the final part of this paper focuses upon the case study of Bôlhâ’s tomb. This monument shows the important role that the banqueting motif played in the familial competition of two groups of descendants, and allows examination of how standardised banqueting images could be made personal and relevant for different individuals.